Studi Evaluatif Pelaksanaan Konsultasi Karir di SMK: Tinjauan dari Perspektif Kolaboratif Guru, Orang Tua, dan Peserta Didik - Rafli, Muhammad; Hidayah, Nur; Wahyuni, Fitri (Jurnal Evaluasi Pendidikan, 2025)
This study evaluates the effectiveness of career consulting program in SMK Negeri 5 Malang with mixed methods approach. Quantitative Data were obtained through Likert scale-based evaluation instruments filled by 4 BK teachers, while qualitative data were collected through Focus Group Discussion (FGD). The results showed an average program implementation score of 81% (good category), with variations in achievement between BK teachers (range 75.71% -90%). Descriptive statistical analysis revealed abnormal data distribution (Shapiro-Wilk p-value <0.001) and standard deviation 0.649-0.857, indicating implementation inconsistency. Qualitative findings show that although the program has been implemented regularly with the involvement of parents and school stakeholders, the evaluation documentation is still oral and need assessment needs to be optimized. The discrepancy analysis model identifies important aspects that are not implemented (Quadrant II) such as written evaluation systems and service standardization. This study concludes that the career consulting program has met the minimum standards that require improvements in documentation and consistency of implementation.